Evaluation of the multidimensional effects of adaptive seating interventions for young children with non-ambulatory cerebral palsy. - Inthachom, Rumrada; Prasertsukdee, Saipin; Ryan, Stephen E.; Kaewkungwal, Jaranit; Limpaninlachat, Sivaporn (Disability & Rehabilitation: Assistive Technology, 2021)
To investigate the short-term effectiveness of the first adaptive seating system received by children with non-ambulatory cerebral palsy (CP) who are classified as level IV or V according to the Gross Motor Function Classification System. A trained clinical assessor examined 20 children with non-ambulatory CP (mean age: 4.5 years) for their trunk control ability in static, active, and reactive tasks using the Segmental Assessment of Trunk Control. Their primary caregivers were also interviewed about their child's activity and participation using the Paediatric Evaluation of Disability Inventory Computer – Adaptive Test in daily activity and social/cognitive domains and Family Impact of Assistive Technology Scale for Adaptive Seating in child and family functioning domains. Data for each measure were collected 3 times: at baseline (pre-intervention) and then 6 weeks and 3 months after children received their first adaptive seating system. The static and active trunk control scores between baseline and 6 weeks, and baseline and 3 months significantly improved. Daily activity scaled scores significantly improved between baseline and 3 months, and 6 weeks and 3 months. Significant, large gains in child and family functioning overall were detected between baseline and 6 weeks, and baseline and 3 months. These findings provide emerging evidence of multidimensional effects associated with the introduction of a first adaptive seating system into the lives of young children with non-ambulatory CP The introduction of an adaptive seating system into the wheelchair of children with non-ambulatory cerebral palsy may be associated with short-term gains in body function, activities, participation and aspects of the child's environment.